Pentosan polysulfate ameliorates proliferation by suppressing the activation of P38MAPK in high glucose-treated HK-2 cells - ZHANG Tian-ying; GUAN Tian-jun; CHEN Ping; XU Bo; YUAN Yang (Linchuang shenzangbing zazhi)
Objective To investigate the effect of pentosan polysulfate(PPS) on diabetic nephropathy renal tubular epithelial cells injury through regulating p38MAPK signaling pathway.Methods Human proximal tubular epithelial cell line(HK-2) cells were grown in media with high glucose concentrationGO,20,30,40 and 50 mmol/L).The rate of cell proliferation was examined by the CCK-8 method.The HK-2 cells were grown in media with high glucose(30 mmol/L) for 30 min,1 h,2 h,4 h,6 h,12 h,24 h and 48 h,and the expression of p38MAPK proteins in the HK-2 cells was analyzed by Western blotting.The HK-2 cells were divided into:controKCON) group,high glucose(30 mmol/L,HG) group,PPS(200 fig/ml) group,HG plus PPS group,p38MAPK inhibitor SB202190(20 μmol/L,SB) group,SB plus HG(SB + HG group),and SB plus PPS group.After pretreatment for 48 h,the rate of cell proliferation was examined.After pretreatment for 6 h,the expression of p38MAPK proteins in the HK-2 cells was analyzed.Results As compared with the CON group,the rate of cell proliferation in the HG group(30 mmol/L) was increased significantly.Simultaneous incubation with PPS inhibited HK-2 cell proliferation(P<0.01 for all).As compared with the CON group,the high glucose increased the phosphorylation of p38MAPK in HK-2 cells for 6 h(P<0.01 for all).The expression of phosphorylated p38(p-p38MAPK) protein in the HG+ PPS group was significantly decreased as compared with that in the HG group(P<0.01 for all).The HK-2 cells were treated with p38MAPK inhibitor SB202190 at the dose of 20 μmol/L for 6 h.As compared with the HG group,the p38MAPK phosphorylation levels in the HG+ SB group was decreased(P<0.05).The expression of p-p38MAPK protein in the PPS + SB group was significantly decreased as compared with that in the PPS group(P<0.05 for all).Conclusions This data demonstrate that blocking p38MAPK signal transduction pathway specifically could inhibit the proliferation of HK-2cells and exert a protective effect on diabetic nephropathy.